Label-free quantitative proteomics and immunoblotting identifies immunoreactive and other excretory-secretory (E/S) proteins of Anoplocephala perfoliata - Hautala, Katja; Pursiainen, Jami; Näreaho, Anu; Nyman, Tuula; Varmanen, Pekka; Sukura, Antti; Nielsen, Martin K.; Savijoki, Kirsi (Frontiers in Immunology, 2022)
Anoplocephala perfoliata is a common tapeworm in horses causing colic and even mortalities. Current diagnostic tests to detect A. perfoliata infections have their limitations and an improved method is needed. Immunoreactive excretory/secretory proteins (E/S proteome) of this parasite can provide promising candidates for diagnostic tests. We compared E/S proteins produced by small (length < 20 mm, width < 5 mm) and large (length 20 to 40 mm, width 5 to 10 mm) A. perfoliata worms in vitro by label-free quantitative proteomics using a database composed of related Hymenolepis diminuta, Echinococcus multilocularis/granulosus and Taenia aseatica proteins for protein identifications. Altogether, 509 E/S proteins were identified after incubating the worms in vitro for three and eight hours. The E/S proteome suggested both worm size- and time-dependent changes in cytoskeleton remodeling, apoptosis, and production of antigens/immunogens. The E/S proteins collected at the three-hour time point represented natural conditions better than those collected at the eight-hour time point, and thereby contained more relevant diagnostic targets. Immunoblotting using antibodies from horses tested positive/negative for A. perfoliata indicated strongest antigenicity/immunogenicity with 13-, 30- and 100-kDa proteins, involving a thioredoxin, heat-shock chaperone 90 (Hsp90), dynein light chain component (DYNLL), tubulin-specific chaperone A (TBCA) and signaling pathway modulators (14-3-3 and Sj-Ts4). This is among the first studies identifying new diagnostic targets and A. perfoliata antigens eliciting a IgG-response in horses.